Cost-Effectiveness analysis of combining plasma Epstein-Barr virus DNA testing and different surveillance imaging modalities for nasopharyngeal carcinoma patients in first remission. (May 2022) - Yang, Zhen-Chong; Nie, Zhi-Qiang; Chen, Qiu-Yan; Du, Chao-Chao; Luo, Dong-Hua; Liu, Li-Ting; Guo, Shan-Shan; Li, Ji-Bin; Sun, Rui; Liu, Sai-Lan; Lu, Zi-Jian; Yuan, Li; et al.
Highlights: The post-radiotherapy (PRT) surveillance strategies combining plasma Epstein-Barr virus (EBV) DNA and different imaging examinations were studied. Clinical follow-up with biannual EBV DNA was cost-effective for the long-term. Surveillance of stage I–II NPC patients with CR. PET/CT strategy should be preferred for patients having IVa NPC with the Chinese WTP threshold of $29, 340. For patients having stage III NPC, PET/CT strategy with ICER of $34, 696 per QALY was acceptable. Abstract: Background: To evaluate the cost-effectiveness of stage-based post-radiotherapy (PRT) nasopharyngeal carcinoma (NPC) surveillance strategies. Methods: Four post-radiotherapy surveillance strategies were established by a Markov model based on data from 1664 patients: 1) clinical follow-up (CFP) with biannual Epstein-Barr virus (EBV) DNA (EBV DNA strategy); 2) CFP with biannual EBV DNA, annual head and neck magnetic resonance imaging (HNMRI), chest X-ray, abdominal ultrasonography, bone scan (only for the first two years) for five years (MCWU strategy); 3) CFP with biannual EBV DNA, annual HNMRI, chest, abdomen, pelvic computerized tomography (CT) and bone scan for the first two years, followed by annual MCWU strategy (without bone scans) for the last three years (CT strategy); 4) CFP with biannual EBV DNA, annual whole-body positron emission/computerized tomography (PET/CT) for the first two years and biannual EBV DNA for the last three years (PET/CT strategy). Results: Compared with the EBV DNA strategy, the MCWU, CT, and PET/CT strategies gained 0.017, 0.047, and 0.082 quality-adjusted life years (QALY) for stage I–II patients. For stage III and IVa patients, the PET/CT strategy had a favorable incremental effectiveness (ICERs) of 0.277 and 0.385 QALY, respectively. The ICERs for the MCWU, CT, and PET/CT strategies were $74, 037, $34, 882, and $34, 696 for stage III and $62, 364, $27, 981, and $28, 340 for stage IVa, respectively. Conclusion: EBV DNA strategy was cost-effective for the long-term surveillance of stage I–II NPC patients with CR. PET/CT strategy was recommeded for patients having IVa NPC. As for stage III NPC, PET/CT strategy was still acceptable with the development of economy in China.